2008
DOI: 10.1007/s10659-008-9163-3
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Peridynamics to Classical Elasticity Theory

Abstract: The peridynamic model of solid mechanics is a nonlocal theory containing a length scale. It is based on direct interactions between points in a continuum separated from each other by a finite distance. The maximum interaction distance provides a length scale for the material model. This paper addresses the question of whether the peridynamic model for an elastic material reproduces the classical local model as this length scale goes to zero. We show that if the motion, constitutive model, and any nonhomogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
239
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 411 publications
(247 citation statements)
references
References 31 publications
7
239
0
1
Order By: Relevance
“…For instance, the recent paper [38] explains that if the underlying deformation is sufficiently smooth, then peridynamics [36,37] is asymptotically equivalent [38] to classical elasticity as the length-scale decreases, and has a symbiotic relationship with molecular dynamics. As a result, a discretized peridynamic model can be implemented using an off-the-shelf molecular dynamic code as described in [32].…”
Section: Blending Methods For Coupling Atomistic and Continuum Modelsmentioning
confidence: 99%
“…For instance, the recent paper [38] explains that if the underlying deformation is sufficiently smooth, then peridynamics [36,37] is asymptotically equivalent [38] to classical elasticity as the length-scale decreases, and has a symbiotic relationship with molecular dynamics. As a result, a discretized peridynamic model can be implemented using an off-the-shelf molecular dynamic code as described in [32].…”
Section: Blending Methods For Coupling Atomistic and Continuum Modelsmentioning
confidence: 99%
“…In addition, a force state similar to the stress tensor in the classical continuum mechanics is introduced. Based on the study of convergence by Silling and Lehoucq [131], it is shown that the peridynamics stress tensor convergences to a Piola-Kirchhoff stress tensor as the length scale goes to zero. Using the state-based peridynamic method, Warren et al [132] presented elastic deformation and fracture of a bar, and Foster et al [133,134] studied viscoplasticity.…”
Section: Peridynamicsmentioning
confidence: 99%
“…Раз-ница заключается в том, что в перидинамической модели силы не локальны. Предельный переход в континуум Коши происходит при r→0 [Silling, Lehoucq, 2008].…”
Section: способы прямой континуализации дискретной средыunclassified